Transition metal nitroprussides: Crystal and electronic structure, and related properties - Reguera, Leslie; Avila, Yosuan; Reguera, Edilso (Coordination chemistry reviews, 2021)
The nitroprusside ion forms 3D, 2D, 1D, 0D and Ionic solids with monovalent and divalent transition metals, which show interesting physical properties among them, spin crossover behavior and ability for the separation and storage of small molecules. [Display omitted] •Coordination chemistry of transition metal nitroprussides.•Electronic structure of transition metal nitroprussides.•Structural diversity of transition metal nitroprussides.•Functional properties of transition metal nitroprussides.•Thermal and environmental stability of transition metal nitroprussides. This review summarizes the state of the art on the structural features, thermal and environmental stability, physical properties and potential applications of transition metal nitroprussides, for their 3D, 2D, 1D and 0D structures. The nitroprusside ion, [Fe(CN)5NO]2−, forms insoluble solids with monovalent and divalent transition metals. The crystal structure for the coordination polymers obtained with divalent metals shows a marked dependence on the used preparative route, metal nature and hydration degree, which was the origin of many incongruities in studies published a few decades ago. Nowadays, the structural features and related properties for the immense majority of the solids formed with such metal ions are known and discussed in this review. The preparation of transition metal nitroprussides using co-ligands with different coordination capability to modulate the dimensionality and related properties of the resulting solids has been on the spotlight of research during the last few years, particularly those related to atypical magnetic behavior. This subject is also herein summarized, revealing the large diversity of hybrid inorganic–organic frameworks that can be obtained with some of their physical properties only recently revealed, among them, the thermal-induced spin transition in ferrous nitroprussides containing monodentate and bridging organic ligands acting as pillar or pseudo-pillars in 2D and 3D hybrid materials. This contribution also includes a general overview of the use of spectroscopic tools such as XPS, XAS, Mössbauer, UV–vis-NIR, IR and Raman, to access electronic and structural characteristics of this family of materials. We also carried out a critical analysis of those research areas that, in our opinion, require further studies, representing opportunities to make important scientific contributions on new knowledge on this family of materials. This is the first general review on transition metal nitroprussides.